(3jJjeI GdOgQ aj eMGSf Cgd GdYUQs - (3YHO Gdedc Hf eMeO Hf ESeGYjd, CHh efUhQ GdKYGdHj,J (B429 (3g` s
(3ChdgG (B:s
(3JHOC HGdbSe GdKGdK (B: (3ai edM CTYGQ Cgd GdLHGd haGQS hLQLGf hWHQSJGf ef hRQGA GdOhdI GdOLdejI , GHf GdYejO s
(3BNQgG (B:s
(3hef eTghQ eG fSH Edjg ef GdTYQ dGYVh di EdG hajg UHGHI acCf GdCYVGA Ndbf bdhHG s
(3fSNI CNQi eLdOI GdeaQi ef fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B163 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B189s
(3eUOQ GbJfGA GdCUd (B:s
(3eOQjO (B(351) s
Keywords: (3GdCOHs